Pengembangan Lembar Kerja Siswa (LKS) Berbasis Ular Tangga Untuk Meningkatkan Hasil Belajar Peserta Didik Terhadap Materi Kegiatan Ekonomi - Ermelinda Alfiani Ikun; Putri Vina Sefaverdiana (Universitas Hamzanwadi, 2022)
This study aims to develop student worksheets (LKS) based on snakes and ladders to determine the feasibility and improvement of student learning outcomes for class VII economic activity material at SMP Bhakti Malang. This type of research is development, the development model used in this study is the 4-D development model which consists of 4 stages, but in this study only uses 3 stages, namely: the define stage, the design stage and the develop stage. Based on the average value of the validation results from each aspect namely; completeness of material, breadth of material, creating curiosity, students' critical thinking skills, all of the criteria are good. The total score from media experts is 41 with a value of 3.41. And material experts score from 58 is 3.86, so that the student worksheets used are declared